CCNA Routing and Switching ICND2 200-105 Official Cert Guide, Academic Edition - Odom, Wendell (Cisco Press, 2016)
Trust the best-selling Official Cert Guide series from Cisco Press to help you learn, prepare, and practice for exam success. They are built with the objective of providing assessment, review, and practice to help ensure you are fully prepared for your certification exam. CCNA Routing and Switching ICND2 200-105 Official Cert Guide, Academic Editionis a comprehensive textbook and study package that provides you with a detailed overview of network configuration and troubleshooting. Best-selling author and expert instructor Wendell Odom shares study hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. This complete study package includes · A test-preparation routine proven to help you pass the exams · "Do I Know This Already?" quizzes, which enable you to decide how much time you need to spend on each section · Chapter-ending and part-ending exercises, which help you drill on key concepts you must know thoroughly · Troubleshooting sections, which help you master the complex scenarios you will face on the exam · A free copy of the eBook version of the text, available in PDF, EPUB, and Mobi (Kindle) formats · The powerful Pearson IT Certification Practice Test software, complete with hundreds of well-reviewed, exam-realistic questions, customization options, and detailed performance reports · A free copy of the CCNA ICND2 200-105 Network Simulator Lite software, complete with meaningful lab exercises that help you hone your hands-on skills with the command-line interface for routers and switches · Links to a series of hands-on config labs developed by the author · Online interactive practice exercises that help you hone your knowledge · More than 50 minutes of video mentoring from the author · A final preparation chapter, which guides you through tools and resources to help you craft your review and test-taking strategies · Study plan suggestions and templates to help you organize and optimize your study time Well regarded for its level of detail, study plans, assessment features, challenging review questions and exercises, video instruction, and hands-on labs, this official study guide helps you master the concepts and techniques that ensure your success. This official study guide helps you master all the topics on the CCNA ICND2 exam, including · Ethernet LANs · IPv4 routing protocols · Wide area networks · IPv4 services: ACLs and QoS · IPv4 routing and troubleshootin ...